North-South Diffusion of a General Purpose Technology - Óscar Afonso (2005)
This paper studies the effects of the diffusion of a General Purpose Technology (GPT), that spreads first within the developed country of its origin (North), and then to a developing country (South). We use a general equilibrium model of growth, where each final good is produced by one of two available technologies. Each technology is characterized by a specific set of intermediate goods complemented by specific labor. The quality of intermediate goods is enhanced periodically by Schumpeterian R&D. When quality reaches a threshold level, a GPT arises in one of the technologies and spreads first to the other one, within the North. Then, it propagates to the South, following a similar sequence. Since diffusion is not even, neither intra nor inter-country, the GPT produces successive changes in the direction of technological knowledge and in inter and intra-country wage inequality.